Effectiveness of Using Work Life Balance Policies within the Directorate General of Treasury - Windhi, Rasvan; Aminah, Shobichatul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to determine the effectiveness of the work-life balance policies implemented in the Directorate General of Treasury of the Ministry of Finance. The focus is on assessing the impact of these programs on employees' in-role performance. A survey was conducted among supervisory and executive staff, with a total of 5,877 employees, resulting in 1,112 respondents. The data were statistically analyzed using SPSS. Correlation analysis was used to determine the correlation between demographic variables, independent variables, and dependent variables, and hierarchical multiple regression analysis was employed to test hypotheses. The results of the data analysis indicate that work-life balance policies do not have a positive and significant effect on employee in-role performance, suggesting that the applied work-life balance policies are not effective. The expected positive implication of this research is to provide insights and perspectives for policymakers regarding the implementation of work-life balance programs to ensure their effectiveness in helping employees balance their work and personal lives.